Characteristics and Mechanism of Pb2+ Adsorption From Aqueous Solution Onto Biochar Derived From Microalgae and Chitosan-Modified Microalgae - Liu, Weigang; Li, Kelin; Hu, Xi; Hu, Xinjiang; Zhang, Ruibin; Li, Qi (Frontiers in Environmental Chemistry, 2021)
With increasing aquatic heavy metal pollution and eutrophication, using algae to prepare novel adsorbent materials for remediating heavy metal pollution has recently attracted research attention worldwide. However, microalgae biochar exhibits poor adsorption capacity in certain conditions, and little is known regarding microalgae biochar modification using chitosan. Chitosan has been previously used to directly modify microalgae biochar; however, in this study, chitosan is used to modify algae powder used to prepare biochar. Therefore, in this study, chitosan was used as a microalgae biochar modifier to enhance its applicability and adsorption capacity. Accordingly, two new types of microalgae biochars, chitosan-biochar (CTS-BC) and biochar-chitosan (BC-CTS), were developed as an adsorbent material using Clostridium and adding chitosan as a modifier at different stages of its preparation. These developed microalgae biochars were characterized using Brunauer–Emmett–Teller surface area,X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and scanning electron microscopy. The adsorption processes of these biochars can be well described by a pseudo-second-order kinetic model. Pb2+ was dominantly adsorbed by microalgal biochar through chemisorption. Following chitosan modification, several mino, cyano, and aromatic ring groups were attached onto the surface of the microalgal biochar. The Pb2+ adsorption capacity of the chitosan-modified biochar was better than that of the unmodified biochar. The maximum Pb2+ adsorption capacity of CTS-BC under acidic conditions (pH = 5) was 9.41 mg g−1, whereas that of BC-CTS under alkaline conditions (pH = 9) was 9.94 mg g−1, both were higher than that of unmodified microalgae biochar under similar conditions. CTS-BC and BC-CTS possessed excellent stability and reusability for Pb(II) adsorption, the adsorption efficiency still remained above 50% even after three cycles. This study demonstrated that adsorbent materials having a stronger heavy-metal adsorption capacity can be prepared by adding chitosan during different stages of the microalgae biochar preparation process.